The Prevalence of Peg Shaped and Missing Permanent Maxillary Lateral Incisors in Najaf City - Raed F. Al-Huwaizi; Anaam Sh. B. Al-Hadad; Abbas F. Al-Huwaizi; Muhsin Hamza Khamis (Kufa Journal for Nursing Sciences)
Background: The presence of a missing or peg shaped lateral incisor is a major concern for the subjects facial esthetics.